Turmoil in Latin America and the Caribbean : volatility, spillovers, and contagion - Perry, Guillermo (World Bank working paper, 2003)
"This report analyzes the potential contagion and spillover effects of the Argentine financial crisis to other Latin American countries. On a country by country basis, the paper assesses the importance of trade and financial linkages as crisis transmission channels between Argentina and other Latin American countries."--Jacket